Dinamika Peradaban Bahasa Arab dan Studi Islam di Masa Sebelum Kenabian (570-610 M) - Masruroh, Shofia Alif; Mubaraq, Zulfi; Kholil, Ahmad; Yansyah, Febri (UIN Sumatera Utara, 2025)
The study of the dynamics of Arabic civilization and Islamic studies during the Pre-Prophetic period (570–610 CE) is highly significant and deserves deeper scholarly attention. This is because discussions surrounding this period continue to generate ongoing academic debate. This paper aims to examine three main aspects. First, the paradigm of Arabic civilization and Islamic studies during the Pre-Prophetic era. Second, the internal and external factors influencing these dynamics. Third, the positive and negative implications of these dynamics during the Pre-Prophetic period. This research employs a library-based method using an article/paper review approach grounded in Harold Lasswell’s theoretical framework. Data were collected through systematic literature review procedures and analyzed using content analysis techniques. The findings reveal three major points. First, the paradigms of Arabic civilization during the Pre-Prophetic period took three forms: (1) tribal solidarity, (2) adherence to Wastani religion (idol worship), and (3) a largely illiterate (ummiy) society. Second, internally, three factors influenced these dynamics: (1) tribal fanaticism and strong loyalty to tradition, (2) dominance in trade and commerce, and (3) eloquence in poetry. Externally, three factors also played significant roles: (1) Jewish and Christian communities, (2) international trade routes, and (3) the noble character of the Prophet Muhammad (peace be upon him). Third, the positive implications of the dynamics of the Arabic language and Islamic studies during this period include: (1) strong social solidarity, (2) moral awareness and a sense of justice, and (3) the development of Arabic as a meaningful and guiding language in life. Meanwhile, the negative implications include: (1) intellectual arrogance, (2) social inequality, and (3) cultural resistance. In conclusion, the dynamics of Arabic civilization and Islamic studies prior to Prophethood constituted a historical foundation that shaped the social, cultural, and intellectual structure of Arab society, while simultaneously paving the way for the emergence of Islamic civilization before the mission of the Prophet Muhammad (peace be upon him).